INCORPORATING MULTIPLE INSTRUCTIONAL APPROACHES IN FOREIGN LANGUAGE TEACHING: DEVELOPING COMMUNICATIVE COMPITENCE (International journal of artificial intelligence, 2026)
Language learning processes are often enhanced through the integration of multiple pedagogical approaches, as different learners benefit from varied methodological input. Combining approaches such as Lexical, Communicative Language Teaching (CLT), Task-Based Language Teaching (TBLT), Content-Based Instruction (CBI), and Competency-Based Language Teaching (CBLT) supports the development of receptive and productive skills. Emphasis on vocabulary development, meaningful communication, and contextualized learning contributes to improved listening, speaking, reading, and writing abilities. Integrated skill development and collaborative learning further enhance learner engagement, motivation, and communicative competence across different proficiency levels.